Memórias e vivências de uma professora formadora de língua portuguesa : reflexões sobre os saberes Xavante nas escolas públicas urbanas de Barra do Garças – MT - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This work is an autobiographical narrative research of a teacher-educator from her experiences, her knowledge and the narrative perceptions of a teacher education experience’s participants, since narrating is to reflect on her own practice and on the other’s, and is related to the human activity, inserting it in contexts of scientific research. The objective of this research is to narrate memories of this teacher-educator and create a narrative-memory constituted by the continuing education course on the teaching of Portuguese Language and Xavante knowledge in urban public schools in Barra do Garças - MT. Our methodological proposal is based on Abrahão (2018); for her, (self) biographed lives are at the limit of the struggle for professional, physical and emotional (re)existence, presenting us with paths such as the permanent narrative as a collective path of reaffirmation of the struggles that move us and the permanent reinvention of life. As a theoretical foundation, this study was based on the context of continuing education that enhances interculturality and indigenous education as a possibility for teaching and recognizing cultural diversity, with authors such as: Lopes de Magalhães and Santos (2016), Couto (2011), Both (2009), Moraes (2015), Munduruku (2005), Assman (1995), Nascimento (2012), Silva (2018, 2021), Rezende (2017, 2020), Walsh (2009), Silvestre (2017) , Ferreira and Benzenger (2020) and Krenak (2015, 2019, 2020). The following sources of empirical material were used: researcher’s personal records and files from the teacher education course “Teaching the Portuguese language and the relationship between teacher and indigenous students in public schools in Barra do Garças-MT”, held virtually from March to May, 2021. Our wish is that the results of this work may be seen as a way of knowing and intervening to improve acting in school spaces, after all, telling their life story and training people from the knowledge of other people open paths, what can (re)signifying teaching practice.
Memories and experiences of a portugueses language teacher trainer : reflections on Xavante knowledge in urban public schools in Barra do Garças - MT
Keywords: Xavante - narrativas; Xavante - saberes; Xavante - formativa; LETRAS::LINGUA PORTUGUESA; CIENCIAS HUMANAS::EDUCACAO